2020
DOI: 10.1016/j.heliyon.2020.e05247
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Musa sapientum Linn. for digestive function promotion by supporting Lactobacillus sp.

Abstract: Lactobacillus is a beneficial bacteria that could inhibit pathogenic potential of other microorganisms. This is the first study to develop a potential tablet from Musa sapientum Linn. (locally known as Kluai Namwa) using the direct compression method to support Lactobacillus sp. We compared the amount of resistant starch and prebiotic properties of the dry powder from unpeeled raw fruit, peeled raw fruit, and starch from M. sapientum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…There was a report on banana starch which had a high RS content (≈75%) with a prebiotic index similar to inulin, a well‐known prebiotic. [ 96 ] The prebiotics normally has a certain degree of polymerization which depends on the type of prebiotics. The most commonly used prebiotics are inulin, fructooligosaccharides, galactooligosaccharides, and isomaltooligosaccharide.…”
Section: The Relation Between the Resistant Starch And Prebioticsmentioning
confidence: 99%
“…There was a report on banana starch which had a high RS content (≈75%) with a prebiotic index similar to inulin, a well‐known prebiotic. [ 96 ] The prebiotics normally has a certain degree of polymerization which depends on the type of prebiotics. The most commonly used prebiotics are inulin, fructooligosaccharides, galactooligosaccharides, and isomaltooligosaccharide.…”
Section: The Relation Between the Resistant Starch And Prebioticsmentioning
confidence: 99%
“…[48,[84][85][86][87] It has been suggested that L. plantarum BSL can reduce liver damage by producing cytokines and antagonistic compounds, reducing the secretion of pro-inflammatory interleukin, and protecting against pathogens. [88,89] Bifidobacterium may contribute to the maintenance of gastrointestinal health, enhancement of barrier function, and immunomodulation. [90,91] Furthermore, S. thermophilus prevents inflammatory bowel disease through increased production of anti-inflammatory (IL-4, IL-5, IL-10) cytokines and reduced secretion of pro-inflammatory IL-1𝛽 and IFN-𝛾.…”
Section: Effect On Gut Microbiota Populationmentioning
confidence: 99%
“…[99] Despite variations in the relative increases in the concentration of SCFAs, BFRS can be classified as a prebiotic as it is fermented selectively and leads to specific changes in gastrointestinal microbiota activity/composition leading to the host obtaining benefits from it. [48,89,94,95,100,114,115] However, although unripe banana flour leads to an increase in SCFAs, the mechanisms underlying the variations in their relative proportions need to be further elucidated. This will facilitate the application of unripe banana flour to address specific health problems, for example, enhancing the proportion of butyrate for colorectal cancer alleviation.…”
Section: Effect On Colonic Short-chain Fatty Acids (Scfas) Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystalline structure was examined by X-Ray Diffraction (XRD). Diffractograms were obtained from 5º-90º (2θ) at a scanning speed of 6ºC/min [13]. The % crystallinity was calculated as [100 × [Ac/(Ac+Aa)]], where Ac is the area of crystalline peaks of diffraction, and Aa is the area of amorphous peaks of diffraction.…”
Section: Thermal Properties and Crystallinitymentioning
confidence: 99%